2004
DOI: 10.1242/jeb.01134
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin B receptor Ca2+ signaling in shark vascular smooth muscle: participation of inositol trisphosphate and ryanodine receptors

Abstract: [Ca 2+ ]i response to ETBR agonist stimulation by a mean of 39%. These data show for the first time that in VSM of the shark, ETBR activation stimulates both IP3R and RyR, and that cADPR is involved in RyR activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
10
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 43 publications
3
10
1
Order By: Relevance
“…As we reported previously, the response of shark VSM cells to ET-1 at cool temperatures is characterized by a broad peak, which falls back to baseline values in approximately 100·s (Fellner and Parker, 2004). Based on the techniques employed in the present study, we found that the mean baseline [Ca 2+ ] i was 116±6 and the peak response to ET-1 was 220±9·nmol·l -1 (N=53, P<0.01; Fig.·1 2+ are wellstudied inhibitors of the ADPR cyclase in vascular smooth muscle (de Toledo et al, 2000;Sethi et al, 1996).…”
Section: +supporting
confidence: 78%
See 4 more Smart Citations
“…As we reported previously, the response of shark VSM cells to ET-1 at cool temperatures is characterized by a broad peak, which falls back to baseline values in approximately 100·s (Fellner and Parker, 2004). Based on the techniques employed in the present study, we found that the mean baseline [Ca 2+ ] i was 116±6 and the peak response to ET-1 was 220±9·nmol·l -1 (N=53, P<0.01; Fig.·1 2+ are wellstudied inhibitors of the ADPR cyclase in vascular smooth muscle (de Toledo et al, 2000;Sethi et al, 1996).…”
Section: +supporting
confidence: 78%
“…Therefore, in the current study we utilized inhibitors of the ADPR cyclase, an inhibitor of NOX and a superoxide dismutase mimetic to investigate how ET-1 might activate the cyclase to generate cADPR. Because our previous investigations of Ca 2+ signaling pathways in shark VSM have demonstrated remarkable concordance with those of mammalian VSM (Fellner and Parker, 2004), we believe that the current study can give insight into the role of superoxide, preserved during evolution, in the responses of VSM to peptide agonists.…”
Section: -supporting
confidence: 60%
See 3 more Smart Citations